2016
DOI: 10.1093/alcalc/agw002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends in Alcohol Dependence and Alcohol Use Disorders in Japanese Adults; Results from Periodical Nationwide Surveys

Abstract: The survey observed many hidden alcoholic patients, and showed the possibility that the healthcare facilities and health screening became the place of screening and intervention for alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 14 publications
7
64
1
Order By: Relevance
“…Smoking rates remain higher among industrialized countries (32.2% in men and 8.5% in women), and tobacco-related cancers and diseases are (and will be) frequent. Although the prevalence of daily drinking is declining, only a small fraction of alcohol-dependent patients had received medical care [10, 11]. Sedentary working style, physical inactivity, and greater motorization are prevailing [10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking rates remain higher among industrialized countries (32.2% in men and 8.5% in women), and tobacco-related cancers and diseases are (and will be) frequent. Although the prevalence of daily drinking is declining, only a small fraction of alcohol-dependent patients had received medical care [10, 11]. Sedentary working style, physical inactivity, and greater motorization are prevailing [10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…First, alcohol consumption was measured based on self-reported doses. However, the prevalence of alcohol dependence diagnosed by ICD-10 was reportedly low at 1.9% for men and 0.2% for women in Japanese individuals [35]. In our study, the exclusion criterion of alcoholic consumption was determined by reference to clinical practice guidelines in Japan [4], and we excluded 1714 (6.97%) individuals; therefore, we believe alcohol consumption probably had a negligible impact (if at all) on our results.…”
Section: Limitationsmentioning
confidence: 72%
“…The United States National Epidemiologic Survey (N = 42 392) showed that the 12‐month prevalence of alcohol dependence was 3.80%, and the lifetime prevalence of alcohol dependence was 12.48% . In Japan, approximately 570 000 adults in the general population of 120 million were classified with alcohol dependence in 2012, making this group one of the largest among the various mental disorders …”
Section: Introductionmentioning
confidence: 99%
“…2 In Japan, approximately 570 000 adults in the general population of 120 million were classified with alcohol dependence in 2012, making this group one of the largest among the various mental disorders. 3 The rewarding effects of addictive substances are mediated by various molecules, and much attention has been given to the effects of G protein-activated inwardly rectifying potassium (GIRK) channels. 4 GIRK channels play an important role in signaling that is influenced by addictive substances.…”
Section: Introductionmentioning
confidence: 99%